E-Learning and continuing education in tertiary health facilities in Lima, Peru - Mendoza-Arana, Pedro Jesús (2020)
Objective. To identify the relationship between organizational factors and individual factors of e-learning, with the use of it for the purposes of continued education of health professionals, in public and private hospitals. Methods. A non-experimental research has been developed, with a correlational scope, with a sample of 134 health professionals of one private and two public hospitals in Lima, Peru. Results. The use of e-learning for continued education is high (over 70%), with an average of 105 daily minutes of access to training content, and that its main modalities are video conferences and online courses. Our resuts suggest that invididual factors are more important than organizational factors as determinants of e-learning for continued education purposes. Conclusions. There is a direct relationship between the use of e-learning resources for continuing professional education and the following individual factors: proficiency in the english language, domain of social networks, internet access. On the other hand, we explored posible relationship between the use of e-learning resources for continuing professional education and the following institutional factors: professional recertification policies, institutional accreditation policies, and incentives for continuous education, concluding there is no evidence of such relationship.